INFLUENCE OF ENTREPRENEURSHIP ORIENTATI ON AND INTERNAL RESOURCES ON BUSINESS PERFORMANCE OF MSMEs (STUDY ON MELINJO EMPING BUSINESS ACTORS IN POJOK VILLAGE, NGANTRU SUBDISTRICT, TULUNGAGUNG REGENCY) - S Suheri; Budi Setiawan; Hery Toiba (Agricultural Socio-Economics Journal, 2021)
The purpose of this study is (1) describing and analyzing the significance of the simultaneous influence of entrepreneurial orientation and internal resources on the business performance of home industry emping melinjo in Pojok Village, (2) describing and analyzing the significance of the influence of entrepreneurial orientation on the business performance of MSMEs home industry emping melinjo in Pojok Village, (3) describing and analyzing the significance of the influence of internal resources on the business performance of MSMEs home industry emping melinjo in The Corner Village. This research was conducted in Pojok Village, Ngantru Subdistrict, Tulungagung Regency with a sample number of 55 people. The results of the study There is a significant influence simultaneously entrepreneurial orientation and internal resources on the business performance of MSMEs home industry emping melinjo in The Corner Village, Ngantru Subdistrict, Tulungagung Regency. There is a positive and significant influence of entrepreneurial orientation on the business performance of MSMEs home industry emping melinjo in Pojok Village, Ngantru Subdistrict, Tulungagung Regency. There is a positive and significant influence of internal resources on the business performance of MSMEs home industry emping melinjo in Pojok Village, Ngantru Subdistrict, Tulungagung Regency.